Rewiring remote urban futures?:Youth well-being in northern industry towns - Stammler, Florian; Adams, Ria Maria; Ivanova, Aytalina (Journal of Youth Studies, 2023)
Many small remote cities in the circumpolar North lose population. Our starting point is that such settlements have a viable future when young people see perspectives for their own well-being there. This article studies such perspectives using cases from northern Russia and northern Finland, based on empirically grounded fieldwork. Emphasising contextuality, we analyse how authorities, civil society and industrial companies provide conditions for youth well-being in northern industrial settlements. The results show, how a viable urban community could look like for young inhabitants: crucial determinants are education, social networks and family ties, nature, housing, comfortable infrastructure, meaningful work, mobility and good health. While many of the results resembled between the case study regions, among the differences in the two countries, we found that in Finland notions of a good life in the North base more on individual preferences than in Russia, where collective notions are more important. In conclusion, we suggest that youth well-being becomes a principal component of concepts of viable urban communities, including but not limited to such cases as Arctic peripheral single-industry towns.